PENINGKATAN PRODUKTIVITAS UBI KAYU MELALUI KEGIATAN DEMONSTRASI FARM DI DESA BAKALAN JUMAPOLO - Efrain Patola, JM Sri Hardiatmi, Siswadi Kharis Triyono & (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2015)
Farmers in the village Bakalan been utilizing dry land and yard by planting cassava in monoculture or intercropped with maize, beans, ground, and sweet potatoes. But cassava productivity is still low at an average of 13 t/ha. Efforts to improve the productivity of cassava has been carried out through the demonstration farm, namely the use of high yielding varieties (varieties Elephant) and biofertilizer Biotamax. The result is an increase in the productivity of cassava varieties Elephant to 53 t/haKeywords : demfarm, productivity, and cassava